Community Education in Jati Mulyo Village Regarding the Use of Empty Oil Palm Bunches Waste as a Media for Growing Oyster Mushrooms - Marviany, Anggi; Ibrahim, Annisa; Khairullah, Mhd. Ikhsan; Minarni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Jati Mulyo Village, located in Dendang Sub-district, East Tanjung Jabung Regency, is mostly occupied by farmers. There is a PT. Argo Tumbuh Gemilang which is available for waste only TKKS. Waste empty palm bunches (TKKS) can be used as a basic material for making mushroom growth media. The purpose of implementing community education activities regarding the utilization of palm oil waste into oyster mushroom growing media is to reduce TKKS waste in Jati Mulyo Village and improve the quality of community knowledge as an effort to reduce palm oil waste into useful products. The implementation method used is Forum Group Discussion (FGD). The results obtained can be stated that the community has an increased understanding after participating in educational activities. Community education on the utilization of palm oil bunch waste is not only important to reduce its negative impact on the environment, but can also create new opportunities for economic growth and sustainable development. This project has increased the community's awareness of the benefits of palm bunch waste as a medium for oyster mushroom cultivation.